Integrating Satellite Observations and Hydrological Models to Unravel Large TROPOMI Methane Emissions in South Sudan Wetlands - Yousef A. Y. Albuhaisi; Ype van der Velde; Sudhanshu Pandey; Sander Houweling (Remote Sensing)
This study presents a comprehensive investigation of Methane (CH4) emissions in the wetlands of South Sudan, employing an integrated approach that combines TROPOMI satellite data, river altimetry, and hydrological model outputs. TROPOMI data show a strong increase in CH4 concentrations over the Sudd wetlands from 2018 to 2022. We quantify CH4 emissions using these data. We find a twofold emission increase from 2018 to 2019 (9.2 ± 2.4 Tg yr−1) to 2020 to 2022 (16.3 ± 3.3 Tg yr−1). River altimetry data analysis elucidates the interconnected dynamics of river systems and CH4 emissions. We identify correlations and temporal alignments across South Sudan wetlands catchments. Our findings indicate a clear signature of ENSO driving the wetland dynamics and CH4 emissions in the Sudd by altering precipitation patterns, hydrology, and temperature, leading to variations in anaerobic conditions conducive to CH4 production. Significant correlations are found between CH4 emissions and PCR-GLOBWB-simulated soil moisture dynamics, groundwater recharge, and surface water parameters within specific catchments, underscoring the importance of these parameters on the catchment scale. Lagged correlations were found between hydrological parameters and CH4 emissions, particularly with PCR-GLOBWB-simulated capillary rise. These correlations shed light on the temporal dynamics of this poorly studied and quantified source of CH4. Our findings contribute to the current knowledge of wetland CH4 emissions and highlight the urgency of addressing the complex interplay between hydrology and carbon dynamics in these ecosystems that play a critical role in the global CH4 budget.